NILAI KEHIDUPAN YANG TERDAPAT PADA ADAT KEBO-KEBOAN DESA ALASMALANG SINGOJURUH BANYUWANGI - Muhammad Hasbullah Ridwan; Dina Lutpiyana (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2023)
Adat as ancestral heritage plays an important role in people's lives. Adat is one of the studies of folklore. At the tip of the island of East Java, there is an area that has a lot of customs, namely Banyuwangi Regency. Banyuwangi Regency is famous for its Using Tribe. One of the famous Using Tribes in Banyuwangi is Singojuruh District. In Singojuruh District there is a kebo-keboan custom, this custom is carried out once a year. The focus of the research in this title is how to prepare and process the implementation of the kebo-keboan custom in Alasmalang Village and how the value of life is contained in the kebo-keboan custom. This study uses a partially oral folklore study. The method used in this study is a type of field qualitative research using data analysis methods, in this case, the researcher takes the title "the value of life contained in the kebo-keboan custom of Alasmalang Singojuruh Village, Banyuwangi". Researchers in obtaining data using observation techniques, interviews and documentation. This research resulted in 12 data from 4 different sources. This data explains the preparation and implementation procession in the kebo-keboan custom in Alasmalang Singojuruh Village, Banyuwangi. And then from the preparatory procession to the implementation of the kebo-keboan custom, there is a life value in it, where the values ??of life are very useful for the people of Krajan Hamlet, Alasmalang Village